Response to Growth and Yield Melon Plant (Cucumis Melo L.) in the Giving of Rabbit Urine and KNO3 - I Ketut Sunadra; Anak Agung Mayun Wirajaya; Ni Luh Komang Sulasmini Mudra; Made Sri Yuliartini; Luh Kartini; I Gusti Bagus Udayana; Ida Bagus Komang Mahardika (SEAS (Sustainable Environment Agricultural Science), 2019)
The purpose of this study was to obtain rabbit urine concentration and the right dose of KNO3 to increase fertility and nutrient availability to get the best growth and yield of melons. This research is a factorial experiment, with a Basic Design Randomized Block Design with 2 factors tried. In the first factor giving rabbit urine consists of 4 levels: U0= without giving urine, U1= giving urine 100 cc L-1 water, U2= giving urine 200 cc L-1 water, U3 = giving urine 300 cc L-1 water. The second factor with 3 levels: K0= without KNO3, K1= dose of 100 kg ha-1 KNO3, K2= dose of 200 kg ha-1 KNO3. 12 combination treatments will be obtained and repeated 3 times. From the analysis, results obtained the interaction between administration of rabbit urine and KNO3 significantly affected the highest fresh weight variable per plant in the combination of 300 cc L-1 water rabbit urine with KNO3 dose of 200 kg ha-1 (U3K2) of 225.02 g and the lowest in combination without urine rabbits with no KNO3 (U0K0) of 158.23 g and this increased 42.21%. The fresh weight of fruit per plant in the administration of 300 cc L-1 rabbit urine water (U3) obtained the highest weight of 851.72 g and the lowest without rabbit urine (U0) of 680.96 g and U3 increased by 25.08% when compared with U0. Fresh weight of fruit per plant at a dose of 200 kg ha-1 KNO3 (K2) obtained the highest weight is 903.21 g and the lowest at no KNO3 (K0) is 651.37 g and the dose of 200 kg ha-1 KNO3 (K2) increased 38,66% compared to without KNO3 (K0).